2006
DOI: 10.1007/s00247-006-0336-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of a cervical osteoid osteoma: a trans-thyroid approach

Abstract: We present a 16-year-old girl with an osteoid osteoma in the vertebral body of C5. Given the difficulty of surgically treating the lesion, radiofrequency ablation was used. Percutaneous needle access to this lesion in the anterior aspect of the cervical vertebral body was limited by the many critical adjacent structures. We present our successful treatment of this lesion utilizing a trans-thyroid needle approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The clinical and technical success rate was 94% after primary ablation and after re ablation of the other 2 patients we finally achieved 100% clinical and technical success rate. Our study showed a favorable outcome compatible to other international studies [17][18][19][20][21][22][23][24][25][26][27][28] . Radiofrequency ablation technique is an effective, minimally invasive and economic method of treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The clinical and technical success rate was 94% after primary ablation and after re ablation of the other 2 patients we finally achieved 100% clinical and technical success rate. Our study showed a favorable outcome compatible to other international studies [17][18][19][20][21][22][23][24][25][26][27][28] . Radiofrequency ablation technique is an effective, minimally invasive and economic method of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Osteoid osteoma were treated by curettage and nidus excision previously. Currently CT guided percutaneous radiofrequency ablation is gaining popularity [17][18][19][20][21][22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…6 Access to critical areas including the cervical spine and hip can be easily attained through a probe, with minimal risk of injuring adjacent vital soft tissue structures. 7,8 Technical success depends on the nidus size, the site involved, the surgeon's skill, the probe temperature, whether the procedure is primary or secondary, and whether a monopolar or bipolar ablation device is used. 9 High-energy delivery techniques provide better pain relief than manual energy control devices.…”
Section: Locationmentioning
confidence: 99%
“…There is also less reverberation artifact and shadowing from a spinal needle compared to primary placement of a large bone biopsy set, which improves visualization of structures deep to the needle. This technique has many applications with biopsies in difficult areas as described in Sutphen et al [3]. As discussed above, myositis ossificans has many causes, most commonly trauma.…”
Section: Discussionmentioning
confidence: 99%
“…4) and safe access utilizing a right posterolateral approach behind the internal jugular vein and carotid artery. Utilizing a technique described by Sutphen et al [3], a 21 G, 20-cm Chiba spinal needle (Cook Medical, Bloomington, IN, USA) was passed under US guidance to the margin of the mass (Fig. 5).…”
Section: Case Reportmentioning
confidence: 99%